PENGARUH USER-RELATED FACTORS TERHADAP KUALITAS HASIL PENGEMBANGAN SISTEM INFORMASI - Sriwidharmanely -; Evi Herlyaminda (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
ACTThis research aims to test the effects of user-related factors to quality of information systemdevelopment result. Researcher analyze six factors of user- related such as: user’s participation asindependent variable, and user-developer’s communication, user’s influence, user’s conflict, user’straining and education, user’s expertise as moderating variables. The samples of this research are35 accademic staffs of faculty in Bengkulu University that use information system, SIAKAD. The datawere analyzed by using Moderating Regression Analysis.The results show that user participation significantly incluence the information systemdevelopment results. Whereas, the user-developer’s communication, the user’s training andeducation are moderating variables on the relationship between user’s participation and the quality ofinformation system development result; while the user’s influence, the user’s conflict, and the user’sexpertise does not moderate this relationship.